Tingkat Kepatuhan Pelaku Usaha Pembudidaya Udang di Provinsi Kepulauan Bangka Belitung - Retfi Wiseli (Akuatik: Jurnal Sumberdaya Perairan, 2022)
The rise of shrimp farming businesses in the Province of the Bangka Belitung Islands at this time, it is deemed necessary to know the level of compliance of shrimp cultivators business actors can be measured by looking at the extent of ownership of basic licensing documents for business permits. The method used in this research is descriptive method which is a method of researching the current status of objects with the aim of providing an overview of the state of the object (shrimp farming business actors) at the present time. Data collection was carried out by collecting primary data using interviews with 48 (forty eight) shrimp ponds in the Bangka Belitung Islands Province (Bangka Regency, West Bangka, Central Bangka, South Bangka and Pangkalpinang City). The results of the study indicate that the level of compliance of shrimp aquaculture business actors is classified as less compliant with a percentage of 31.25%. The Compliance Level of Shrimp Farming Business Actors the lowest is Bangka Regency South with a compliance level of 16.67%‎ (low) and the highest level of Compliance of Shrimp Farming Business Actor is Pangkalpinang City with 66 compliance level, 67%‎(quite obedient).‎